(untitled) (Revista Inclusiones, 2020)
In this paper, the attempt of conceptual description of polymer composite materials as dispersed systems on the example of polymer latexes has been made. The pronounced similarities, like interphase boundary as well as difference in hydrophilic and hydrophobic properties of solid phase and medium allows to apply similar approaches to these systems.